Template -free assembly in living bacterial suspension under an external electric field - Samantaray, Kunal; Bhol, Prachi; Sahoo, Bhaban; Barik, Subrat Kumar; Jathavedan, Kiran; Sahu, Bikash Ranjan; Bikash Ranjan; Suar, Mrutyunjay; Bhat, Suresh K.; Mohanty, Priti Sunda (ACS Omega, 2017)
Although template-assisted self-assembly methods are very popular in materials and biological systems, they have certain limitations such as lack of tunability and switchable functionality because of the irreversible association of cells and their matrix components. With an aim to achieve more tunability, we have made an attempt to investigate the self-assembly behavior of rod-shaped living bacteria subjected to an external alternating electric field using confocal microscopy. We demonstrate that rod-shaped living bacteria dispersed in a low salinity aqueous medium form different types of reversible freely suspended structures when subjected to an external alternating electric field. At low field strength, an oriented phase is observed where individual bacterium orients with its major axis aligned along the field direction. At intermediate field strength, bacteria align in the form of one-dimensional (1D) chains that lie along the field direction. Further, at high field strength, more bacteria associate with these 1D chains laterally to form a two-dimensional (2D) array. At higher bacterial concentration, these field-induced 2D arrays extend to form three-dimensional columnar structures. These results are discussed in the context of previously reported studies on bacterial self-assembly.
Keywords: Bacteria; Electric Properties; Self- Assembly

Alternating electric-field-induced assembly of binary mixtures of soft repulsive ionic microgel colloids - Jathavedan, Kiran; Bhat, Suresh K.; Mohanty, Priti S. (Journal of Colloid and Interface Science, 2019)
An external alternating electric field is used to study the assembly of a binary mixture of Poly(N-isopro pylacrylamide-co-acrylic acid) microgels in their swollen form at hydrodynamic size ratio 2:1 under deprotonated state. The AC field experiments were carried out at a fixed frequency of 100 kHz in the fluid regime for three number density ratios 1:3, 1:1 and 3:1 of big-to-small microgels using a confocal microscope. Strings with different types of co-assembly structures such as buckled, ring, flame and sandwich have been observed at low and intermediate field strengths at ratio 1:3, 1:1. In buckled and ring type, one or two small particles sit at the contact of two big particles and in the flame type, small particles arrange like a cone at end of the string. In the sandwich structure, several double small particle layers lie in between big particles. At high field strength, aggregation of strings and a phase separation into individual aggregates of strings from both big and small microgels have been observed. At higher ratio 3:1, the string formation is mostly dominated by big particles. Our experimental results are discussed with the recent simulation and experimental works on AC field induced structures in binary hard sphere mixtures. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: assembly; dipolar interactions; Microgels; Soft colloids